2007
DOI: 10.1152/physiolgenomics.00020.2006
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic regulation in the lactating mammary gland: a lipid synthesizing machine

Abstract: The mammary gland of the lactating mouse synthesizes and secretes milk lipid equivalent to its entire body weight in a single 20-day lactation cycle, making it one of the most active lipid synthetic organs known. We test the hypothesis that multiple control points and potential regulatory mechanisms regulate milk lipid synthesis at the level of gene expression. The mammary transcriptome of 130 genes involved in glucose metabolism was examined at late pregnancy and early lactation, utilizing data obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
256
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(304 citation statements)
references
References 46 publications
38
256
1
9
Order By: Relevance
“…Indeed, if this is true for MECs, it would be compatible with higher lactose in the milk of lipid-deprived rats. Supporting this, it has recently been shown that expression of both hexokinase and glucose phosphate isomerase is downregulated in mouse at the initiation of lactation (Rudolph et al, 2007). This would favour the partitioning of glucose towards lactose production by decreasing its consumption for glycolysis, in the pentose phosphate cycle and the hexosamine biosynthetic pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, if this is true for MECs, it would be compatible with higher lactose in the milk of lipid-deprived rats. Supporting this, it has recently been shown that expression of both hexokinase and glucose phosphate isomerase is downregulated in mouse at the initiation of lactation (Rudolph et al, 2007). This would favour the partitioning of glucose towards lactose production by decreasing its consumption for glycolysis, in the pentose phosphate cycle and the hexosamine biosynthetic pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Our previous study has shown a significant inhibition on ACCα expression by PPARγ knockdown . It is generally believed that SREPB1 plays a key role in regulation of mammary lipogenesis including mice (Rudolph et al, 2007), sheep (Hussein et al, 2013) and dairy cows (Harvatine et al, 2009). In general, the expression of SREBP1 is decreased to even a greater extent than the expression of several lipogenic genes, including the ones measured above, along with those associated with triglyceride assembly and desaturation (Harvatine et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 1 are reported the temporal patterns of transcription of caseins, alpha-lactalbumin, whey acid protein, and albumin from pregnancy to lactation in two ruminant species (dairy cow [89] and dairy goat [90]), two monogastric species (mouse [91] and pig [92]), and a marsupial (kangaroo; Macropus eugenii [93]). Those were the only microarray datasets publicly available at the time of this writing.…”
Section: Mrna Abundance and Expression Patterns Of Transcripts Codingmentioning
confidence: 99%